India’s Vaccine Diplomacy and Global Health Governance: A Soft Power Approach in the Context of Public Policy and Religious Values - Mondal, Joyprokash (Religion and Policy Journal, 2024)
Research Problem: India's vaccine diplomacy during the Covid-19 pandemic has not only emerged as a significant tool of soft power but also involves moral and ethical dimensions closely tied to religious values and public policy. In the midst of a global crisis, the interaction between India’s vaccine diplomacy and the religious and public policy frameworks of recipient nations requires deeper exploration. Research purposes: This article aims to analyze the role of India’s vaccine diplomacy in relation to public policy and religious values in recipient countries, examining how India’s global health initiatives influence moral and ethical perceptions of vaccine distribution, fairness, and international solidarity. Research methods: The study employs policy analysis through a comprehensive literature review, focusing on the relationship between vaccine diplomacy, public policy, and responses from religious communities in the recipient countries. It also explores the ethical and spiritual dimensions of India’s health diplomacy approach and its impact on public health policies. Results and Discussion: The findings reveal that India’s vaccine diplomacy, through initiatives like "Vaccine Maitri," not only strengthens political ties with neighboring and global countries but also interacts with religious value systems, influencing public acceptance of vaccines. Moral values such as solidarity and justice, integral to many religious traditions, reinforce positive responses to the vaccine initiatives. Additionally, in some nations, religious communities have played a significant role in promoting vaccine acceptance by framing the health response in moral terms. Research Implications and Contributions: This research highlights the importance of integrating religious values into public health policy, particularly in global health contexts. Vaccine diplomacy rooted in moral solidarity and universal ethical principles, aligned with religious values, has the potential to enhance international cooperation and reduce vaccine hesitancy. Thus, this study contributes to understanding how religion and public policy can collaborate effectively in addressing global health challenges.